Sleep disordered breathing (SDB) experiences associated with snoring in adult Nigerians - Sogebi, OA (Makerere Medical School, 2011)
BACKGROUND: Snorers often experience symptoms of sleep disordered breathing (SDB) which is largely undiagnosed in the population. Information on SDB experiences is needed to target high-risk individuals that may benefit from treatment of snoring. OBJECTIVE: This study compares the experience of the nighttime and daytime symptoms of SDB of habitual snorers with that of non-habitually snoring adult subjects in a tertiary health facility in Nigeria. METHODS: A cross-sectional, comparative, hospital based study was conducted. Berlin questionnaire was administered to consecutive adult patients (subjects) attending ENT Clinic of OOUTH, Sagamu, Nigeria. Based on the responses to their experience of snoring, the subjects were categorized as habitual snorers or non-habitual snorers. General physical examinations with emphases on the nose, throat and neck were performed on the subjects. The experiences of nighttime and daytime symptoms of SDB were recorded and those of habitual snorers compared to non-habitual snorers. RESULTS: One hundred and ninety- five subjects participated in the study. M:F =1.3:1. Overall prevalence of snoring was 37.9% and habitual snoring was 18.5%. Habitual snoring was significantly associated with age, marital status and obesity (BMI>=30.0). There were statistically significant increased odds of experiencing the nighttime and daytime symptoms of SDB in habitual snorers compared to non-habitual snorers. CONCLUSION: Adults that snore habitually had significantly more nighttime and daytime symptoms of SDB compared to those who do not snore habitually. Habitual snoring predisposes adult subjects to experiencing symptoms of SDB.